I do [videorecording (DVD)] - Ross, David W.; Ross, David W.; Witt, Alicia, 1975-; Sigler, Jamie-Lynn, 1981-; Bowler, Grant, 1968- (Breaking Glass Pictures, 2013)
A gay Brit living in New York is deprived of his immigration status and risks losing his family and life in the U.S. He marries his lesbian best friend to remain in the country and stay with his family, but things get complicated when he meets the love of his life and is forced to make an impossible choice.